NAVIGATING THE CHALLENGES OF UNCONTROLLED THYROTOXICOSIS - Padzil, Mohd Hafiz Mohd; See, Chee Keong; Shudim, Saiful Shahrizal (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Thyrotoxicosis is a condition characterized by the excessive production of thyroid hormones. Commonly presented as Graves’ disease, other aetiology includes toxic multinodular goitre or subacute thyroiditis. Therapeutic approaches depend on the aetiology which includes anti-thyroid medications, radioactive iodine, or surgical intervention. We highlight 2 cases with different aetiologies of thyrotoxicosis that remained uncontrolled despite medical therapy and necessitated surgical intervention. CASE 1 23-year-old female with diffuse goitre that was progressively increasing in size since the age of 15. She presented with classic thyrotoxicosis symptoms. She was confirmed to have Graves’ disease and was treated with carbimazole therapy. However, she remained uncontrolled after 2 years despite high dose carbimazole therapy (90 mg/ day), lithium (600 mg/day), prednisolone (20 mg/day) and cholestyramine. She finally relented to surgical intervention as her definitive treatment. Her perioperative optimization was equally challenging and the addition of Lugol’s iodine a week prior to surgery brought her free T4 levels below 20 pmol/L. Through multidisciplinary collaboration between endocrinologists, surgeons and anaesthetists, she had a successful total thyroidectomy. CASE 2 A 58-year-old female presented with a 7-year history of toxic multinodular goitre before her referral to our centre. She had been receiving fluctuating doses of carbimazole and her TFT remained uncontrolled. She also had retrosternal thyroid extension with mass effect. Her TFT remained uncontrolled despite carbimazole 25 mg/day, and coupled with compressive symptoms, navigated us towards definitive surgical intervention. Timely Lugol’s iodine treatment optimized her TFT preoperatively and she successfully underwent total thyroidectomy. CONCLUSION Both cases highlighted the difficulty in managing thyrotoxicosis and surgical intervention was the best definitive treatment. Perioperative preparation is often challenging requiring multimodal approach to lower free T4 to acceptable levels prior to definitive thyroidectomy